Fondasi dan Implementasi Hukum Ekonomi Syariah dalam Kehidupan Modern - Fatma, Fitrotul Maulida (Maliki Interdisciplinary Journal, 2025)
Sharia economic law is a set of economic rules based on Islamic law, aimed at creating justice, balance and sustainability in economic activities. This article aims to describe the definition, legal sources, basic principles, and implementation of sharia economic law in various sectors. Apart from that, this article also examines the challenges and opportunities for its implementation in the modern era. The method used in this research is Library Research by collecting data through books, articles and journals. an economic system based on the values ​​of justice, transparency, and balance. This foundation makes sharia economics a relevant alternative amidst the challenges and instability of the global economy. In modern life, sharia economic law has been successfully implemented through various instruments such as sharia banking, halal insurance, and sharia fintech.